2019
DOI: 10.1038/s41598-019-39525-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of ATM mutations in patients with metastatic colorectal cancer

Abstract: Tumors bearing homologous recombination deficiency are extremely sensitive to DNA double strand breaks induced by several chemotherapeutic agents. ATM gene, encoding a protein involved in DNA damage response, is frequently mutated in colorectal cancer (CRC), but its potential role as predictive and prognostic biomarker has not been fully investigated. We carried out a multicenter effort aimed at defining the prognostic impact of ATM mutational status in metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…The TCGA and MSKCC dataset reported that ATM mutations were detected in 14% and 7% of CRC patients, respectively. Randon et al found that ATM mutations are independently associated with longer OS in patients with metastatic CRC [26]. However, we revealed that ATM mutation is linked to poorer OS in patients with CRC.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The TCGA and MSKCC dataset reported that ATM mutations were detected in 14% and 7% of CRC patients, respectively. Randon et al found that ATM mutations are independently associated with longer OS in patients with metastatic CRC [26]. However, we revealed that ATM mutation is linked to poorer OS in patients with CRC.…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, no differences were observed in the OS according to ATM mutation status in both TCGA and MSKCC cohorts. The discrepancy among studies might be due to the different prognostic role of ATM according to the disease stage and the confounding factors from the heterogeneity of available treatment strategies used for metastatic disease [26].…”
Section: Discussionmentioning
confidence: 99%
“… 37 They are associated with increased platinum sensitivity and superior survival. 37 , 38 Tumors with loss-of-function ATM mutations have increased radiosensitivity. 39 ATM suppression in the setting of p53 deficiency sensitizes tumors to DNA-damaging chemotherapy and radiotherapy, whereas ATM suppression with intact p53 leads to a worse response.…”
Section: Molecular Tumor Board Discussionmentioning
confidence: 99%
“…Reduced protein expression of ATM has been suggested as a biomarker of poor RFS in CRC stage II/III [29], supporting the potential importance of ATM, C11ORF65 as a prognostic marker noticed here. In the context of metastatic disease reduced ATM protein expression, as well as genetic variants of ATM, have been related with increased chemosensitivity to oxaliplatin-based therapy and overall survival [30,31]. However, the concordance between protein loss and presence of genetic variation, when described, was relatively weak [30].…”
Section: Discussionmentioning
confidence: 99%